KOMUNIKASI, INFORMASI, EDUKASI PENYAKIT HIPERTENSI SEBAGAI STRATEGI UNTUK MENINGKATKAN PENGETAHUAN MASYARAKAT DI KELURAHAN PAKANSARI CIBINONG, KABUPATEN BOGOR - Herlina, Nina; Fatmi, Mindiya; Ambarwati, Rini; Andini, Septia; Rokhmah, Nisa Najwa; Nurmala, Sara; Nurhikmah, Wilda; Wahyuningrum, Cintya; Rikkit (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Hypertension is a significant health issue in Indonesia, with a prevalence of 30.8%. This community service activity aims to enhance the knowledge of residents in Pakansari Village regarding hypertension and its management through education on dietary patterns and using fruits and vegetables. The methods employed in this activity include Information and Education Activities, which consist of presentations, discussions, practical sessions on making healthy juices from local ingredients, and counseling. The results indicate an improvement in participants' knowledge, with an average post-test score reaching 95%, compared to a pre-test score of 88%. Additionally, participants successfully practiced making healthy beverages that can be incorporated into their daily routines to help control blood pressure. This activity will positively impact community health and encourage healthier lifestyle changes.